Job specification on facilities management of local authorities and its relation towards tenant satisfaction in Kelantan / Nadzirah Athirah Karim and Nor Nazihah Chuweni - Karim, Nadzirah Athirah; Chuweni, Nor Nazihah (2019)
Facilities Management is significant for any local authorities in providing adequate and sufficient services to its community. Facilities Management is not only focused on managing the building to reduce the cost of maintenance, but also need to provide the satisfaction among the users in the building with efficient services. The organization who responsible to ensure that the services been delivering to the users need to understand clearly the function of the managing the facilities in the local authorities. This study aim to determine the level of tenant satisfaction towards facilities management of local authority and to identify the existing job specification among local authority officers involved in facilities management. 100 questionnaires have been distributed to the tenants who rented out the building under local authorities namely Pasar Siti Khadijah, Pasar Siti Fatimah and Pasar Besar Bandar Tasek Raja from two different districts. Interviews have been conducted with two officers from Kota Bharu Municipal Council (KBMC) and Pasir Mas District Council (PMDC). The results show that there are need of improvement in building maintenance of the building to fulfill the tenant satisfaction and understanding the job specifications among officers in delivering the services.